PENYUSUNAN DAN PENGISIAN PERMOHONAN PINJAMAN DAN PERJANJIAN KREDIT (BUMDes) DI DESA POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The report entitled "Preparation and Completion of loan application letters, credit agreements, cash disbursement orders (BUMDes) in Pomahan Village, Pulung District, Ponorogo Regency" This is one of the requirements for the Job Training (KKN) in each work program that has been completed in Pomahan village, Pulung District, Ponorogo Regency, East Java.Preparation and Completion of loan application letters, credit agreements, cash disbursement orders are useful for BUMDes treasurers, in addition to customers who will borrow money at BUMDes, and for us run KKN work programs and aim to share information on the many benefits of System Preparation for the Bumdes management in Pomahan village.In this report we explain how to borrow money on BUMDes, which begins with filling in the post test and pre-test of the management, presentation of the material by myself and closing with a group photo. After Preparation and Completion of the loan application letter, credit agreement, cash disbursement order (Bumdes), BUMDes management knows the order of the loan letter